Control of cell behaviour through nanovibrational stimulation: nanokicking. (16th April 2018) - Robertson, Shaun N.; Campsie, Paul; Childs, Peter G.; Madsen, Fiona; Donnelly, Hannah; Henriquez, Fiona L.; Mackay, William G.; Salmerón-Sánchez, Manuel; Tsimbouri, Monica P.; Williams, Craig; Dalby, Matthew J.; Reid, Stuart
Abstract : Mechanical signals are ubiquitous in our everyday life and the process of converting these mechanical signals into a biological signalling response is known as mechanotransduction. Our understanding of mechanotransduction, and its contribution to vital cellular responses, is a rapidly expanding field of research involving complex processes that are still not clearly understood. The use of mechanical vibration as a stimulus of mechanotransduction, including variation of frequency and amplitude, allows an alternative method to control specific cell behaviour without chemical stimulation (e.g. growth factors). Chemical-independent control of cell behaviour could be highly advantageous for fields including drug discovery and clinical tissue engineering. In this review, a novel technique is described based on nanoscale sinusoidal vibration. Using finite-element analysis in conjunction with laser interferometry, techniques that are used within the field of gravitational wave detection, optimization of apparatus design and calibration of vibration application have been performed. We further discuss the application of nanovibrational stimulation, or 'nanokicking', to eukaryotic and prokaryotic cells including the differentiation of mesenchymal stem cells towards an osteoblast cell lineage. Mechanotransductive mechanisms are discussed including mediation through the Rho-A kinase signalling pathway. Optimization of this technique was first performed in two-dimensional culture using a simple vibration platform with an optimal frequency and amplitude of 1 kHz and 22 nm. A novel bioreactor was developed to scale up cell production, with recent research demonstrating that mesenchymal stem cell differentiation can be efficiently triggered in soft gel constructs. This important step provides first evidence that clinically relevant (three-dimensional) volumes of osteoblasts can be produced for the purpose of bone grafting, without complex scaffolds and/or chemical induction. Initial findings have shown that nanovibrational stimulation can also reduce biofilm formation in a number of clinically relevant bacteria. This demonstrates additional utility of the bioreactor to investigate mechanotransduction in other fields of research. This article is part of a discussion meeting issue 'The promises of gravitational-wave astronomy'.